2012
DOI: 10.1002/pssa.201228190
|View full text |Cite
|
Sign up to set email alerts
|

Formation of atom‐sized contacts of Mg and Mg alloys at room temperature

Abstract: We have measured the conductance of atom‐sized contacts of dilute MgZnCa and MgZnCe alloys at room temperature (RT) and found two new peaks at (1.6–1.7)G0 and (2.6–2.9)G0 (where $G_{0} \equiv 2e^{2} /h$ is the quantum unit of conductance) in their conductance histograms. Because the solute level in these alloys is too low to affect the contact conductance, these peaks can be considered as low‐conductance peaks of pure Mg, which have not been observed in the histogram of pure Mg at RT [Smit et al., New J. Phys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
4
6
0
Order By: Relevance
“…Presumably, necking deformations of most HCP junctions would be curtailed by premature fracture and cannot produce SACs at RT. The importance of junction deformation on the SAC formation has been invoked for explaining the missing SAC peak of Ga [3] and also indicated in our previous experiment [10] where we measured the conductance of Mg alloys of high ductility and found a couple of low conductance peaks that are missing for ordinary Mg.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Presumably, necking deformations of most HCP junctions would be curtailed by premature fracture and cannot produce SACs at RT. The importance of junction deformation on the SAC formation has been invoked for explaining the missing SAC peak of Ga [3] and also indicated in our previous experiment [10] where we measured the conductance of Mg alloys of high ductility and found a couple of low conductance peaks that are missing for ordinary Mg.…”
Section: Introductionsupporting
confidence: 62%
“…The experimental setup and measurement procedures are mostly the same as those used in our previous experiment on Mg alloys [10]. Our electrodes are a pair of short pieces of wire, the diameter and purity of which are 1 mm and 99.999% for Cd and 1 mm and 99.99% for Ti, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Missing of the single‐atom peak in a histogram at 300 K has also been reported in break‐junction experiments on Zn () and Ga (). Clearly, the necking deformation of these non‐FCC metal NWs should be different from that of Au and somehow incapable of forming single‐atom contacts at 300 K. In our previous work (), we carried out break‐junction experiments on special Mg alloys of high ductility and retrieved a couple of low‐conductance Mg peaks that were missing in the conductance histogram of ordinary Mg at 300 K. This result confirms that the deformation characteristics of Mg NWs should be a key factor for the formation of Mg single‐atom contacts at 4 K and their absence 300 K. To obtain some insights on this problem, we have carried out MD simulations of the break of Mg NWs and studied their necking deformations at 4 and at 300 K. MD simulations have been extensively used in the past for examining deformations of various metal NWs. All previous studies have, however, been made on FCC metals and no break simulations on BCC and HCP NWs.…”
Section: Introductionsupporting
confidence: 58%
“…On the other hand, NCs of other metals including most of d-electron metals do not show the quantization features of the conductance. For example, in magnesium 66 , cobalt 67 , niobium 47 , tungsten 68 , and only one or a few broad peaks are observed in their conductance histograms. Zr is categorized into the latter and the present study confirmed this.…”
Section: Discussionmentioning
confidence: 99%